Prey of the Great Horned Owl (Bubo virginianus) in the lower delta of the Paraná River (Buenos Aires, Argentina) - Teta, P. (2006)
Fil:Quintana, R. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.